Mobile technology trends and their potential for agricultural development - Heike Baumüller (University of Bonn, Center for Development Research (ZEF), 2013)
Mobile phones have spread around the developing world at an amazing speed. Their proliferation has given rise to numerous mobile phone-enabled services (m-services) in the areas of health, education, agriculture and entertainment. However, to date many of these services are barely scratching the surface of what is technologically possible. This paper examines the potential of recent mobile technology trend to enhance the functions and reach of m-services, with a focus on promoting agricultural development among smallholder farmers. To this end, the paper identifies three broad trends: the growing diversity of devices to access mobile content and functions, the Internet of Things that links sensors and 'smart objects', and the power of social networks and a large user base to gather data, collectively develop solutions and facilitate learning. For each of these trends, the paper reviews the current state of the technologies and highlights actual and potential applications in the agriculture sector. The extent to which benefits can be realised on a large scale will depend on a number of factors. Thus, the paper outlines two possible scenarios how the trends could evolve in the future under different assumption and assesses the implications of these scenarios for the provision of m-services that suit the needs and capacities of farmers in developing countries.
Keywords: 330; agriculture; mobile phones; mobile connected devices; m-services; internet of things; cloud computing; big data; crowdsourcing; social networks